BIOMASSA E CARBONO EM ESPINILHO (Vachellia caven (Molina) Seigler e Ebinger) - MOREIRA, VANESSA SILVA (2016)
Despite occupying a prominent place in Rio Grande do Sul flora, the area belonging to the study, is inserted into the phytogeographic areas of Savannah Estépica Park is not well studied and investigated by the science. Taking advantage of this fact, this study aimed to solve Allometric equations to quantify the tree aboveground biomass and carbon stored in trees Vachellia caven (Molina) Seigler and Ebinger (Espinilho) in their different components of the inserted fragment in the RS campaign . To this end, a representative area was selected for the study in 1 ha, subdivided into five subunits sample of 2000 m², there was the forest census and dendrometric variables (height and diameter) were measured. a total of 310 trees were identified, selected trees showed the diameter ≥ 7 cm, obtaining a total of 229 individuals. They were felled 30 trees sampled for the settlement of allometric equations for biomass and 12 trees for analysis of carbon content. Trees were felled and sectioned in magazines: stem wood, bark, leaves and twigs. Next, each component of a sample was taken for dry matter and carbon determination. In addition to the determination of biomass and carbon, the database contained the dendrometric measured as the total height (ht) and the diameter 30 centimeters, which were used as independent variables. In order to obtain estimates of biomass and carbon weight in the different compartments of the tree through variable dendrometric, were used 20 models commonly used in the literature. For biomass equations were observed good results in adjustments to the overall tree with the best determination coefficient equal to 0.7064 and the standard error equal to 36.22% and the shank of the best R2aj was 0.8491 and Sxy equal to 36.93%. In adjustments to the shell, the results were due to peeling median be a very thick dead tissue, and irregular cracks, causing a change in diameter that is one of the measured variables dendrometric. As to the twigs R2aj varies from 0.1562 to 0.1967 and Sxy ranging from 61.12% to 84.46% and leaves the best determination coefficient equal to 0.0895 and the standard error equal to 40.65% the equations adjusted for these two compartments had the lowest accuracy in estimates. The results show the importance of Espinilho this Savana Estépica fragment to carbon sequestration from the atmosphere and as an energy source (coal and wood) which is of utmost importance to forests in general also has a great importance in order the preservation and maintenance of these areas lying in an endemic in Brazil environment occurs only in RS, making a conversation unit and a typical vegetation is not quenched.